Effect of rheological heterogeneities on the lithospheric deformation of the Tibetan Plateau and neighbouring regions - Sun, Yujun; Li, Hailong; Fan, Taoyuan; Li, Bing (Frontiers in Earth Science, 2023)
The Tibetan Plateau, induced by the India-Eurasian collision, has the highest average altitude in the world. During its uplift in vertically, the Tibetan Plateau has been considered to expand laterally. However, there are several strong and almost non-deformable cratons on its periphery, such as the Tarim, North China craton and South China block. The present landform features show that these cratons limit the expansion of the Tibetan Plateau. However, there is still much controversy over whether the deformation can be transmitted to periphery orogens or reactivate ancient orogens in the cratons. This study used numerical models to investigate the effect of rheological heterogeneities on the lithospheric deformation of the Tibetan Plateau and its neighbouring regions. The results show that the lateral heterogeneities of the lithosphere have an important influence on the deformation or strain partitioning. Generally, during the lateral expansion of the Tibetan Plateau, its peripheral cratons can transmit the deformation or high strain to neighbouring weak orogens. This case can be used to understand the Tian Shan orogen, which was reactivated by the India-Eurasian collision. However, when the orogens inside the cratons have high lithospheric strength, high strain is difficult to distribute on them and the expanding Tibetan Plateau is constrained by its peripheral cratons. These results can be used to explain the ancient orogens that are not strongly deformed, such as the Jiangnan orogen in the South China block. Because these orogens formed at the same time as the cratons and have relatively high lithospheric strength. In addition, the large lithospheric thickness difference and low crustal rheological contrast favor high strain rate localized on the lithosphere of the ancient orogen in the craton, such as the Trans-North China orogen in the North China craton.